Socioeconomic status, social‐cultural values, life stress, and health behaviors in a national sample of adolescents. (29th January 2019) - Milas, Goran; Klarić, Irena Martinović; Malnar, Ana; Šupe‐Domić, Daniela; Slavich, George M.
Abstract: Adolescence is a developmental period during which time individuals adopt health behaviors that affect their lifelong health and disease risk. Socioeconomic status, social‐cultural values, and stress have all been hypothesized to play a role in this association, but very few studies have examined how these factors interrelate and explain differences in health behaviors in adolescence. To address this issue, we assessed youths' socioeconomic status, social‐cultural values, life stress levels across seven domains, and health behaviors in a national sample of 1, 830 high school seniors living in the four largest cities in Croatia. Structural equation modelling examined the extent to which stress mediates the effects of socioeconomic status and social‐cultural values on positive and negative health behaviors. As hypothesized, stress levels significantly mediated associations between youths' socioeconomic status, social‐cultural values, and healthy and unhealthy habits. Additionally, whereas better socioeconomic status predicted less stress, greater social‐cultural value on achieving a "good life" predicted more stress. More stress, in turn, was associated with engaging in fewer healthy behaviors for both males and females, and more unhealthy behaviors for males. Socioeconomic status and social‐cultural values thus appear to influence stress levels, which may in turn affect adolescents' health behaviors and, potentially, their lifespan health.